SECONDARY SCHOOL STUDENTS’ PERCEPTIONS TOWARD THE USE OF EFFECTIVE PLATFORM IN ONLINE LEARNING DURING COVID_19 OUTBREAK - Uswatun Hasanah (Graduate Program, University of Islam Malang, 2021)
The purposes of this study, were to find out the perceptions of secondary school students toward the use of platforms in online learning and the most effective one during Covid-19 outbreak. Descriptive quantitative research design was used to collect the data. The subjects were one hundred and twenty-four students of Senior High School One Kraksaan. The data was gathered through a questionnaire, an interview, and documentation. Students have positive perspectives of the effective platform used in online learning during the Covid-19 outbreak, based on the current research. The majority of students agree that the platform used for online learning during the Covid-19 outbreak was beneficial.While, students’ perception on the most effective platform are, Google meet and zoom. They think that learning through a video is much more effective rather than just providing learning material through Google Classroom, for example if there is a learning material, they don’t understand they can ask their teacher immediately, besides that Google form and quizizz are considered as the most simple and practical one, Since, they do not need to use paper in taking exams. It also creates a new learning environment, ensuring that kids are not bored while doing the tasks provided by the platforms. Keyword: Students Perceptions’, Effective Platform, Online learning, Covid-19 outbreak.